The European Union and member state territories: A new legal framework under the EU treaties - Murray, Fiona (T. M. C. Asser Press, 2012)
The book reviews the EU Treaties provisions governing relations between the EU and Member State territories, such as the Netherlands Antilles, the UK Channel Islands and the French Overseas Departments. The book includes an overview of each of the relevant territories, including their present constitutional relations with their Member State and their legal relations with the EU. Prior to the entry into force of the Lisbon Treaty, the over-arching Treaty provision for this relationship was Article 299 of the EC Treaty. Having traced the development of Article 299 from 1957 to the present Lisbon framework, the book identifies many inconsistencies and issues with this current framework and proposes a new model framework, one that is more concise and up-to-date and which is adaptable to possible future developments. A useful book for EU Law departments and research centres, EU think tanks, EU institutions libraries, Permanent Representatives to the EU and law firms specializing in EU law.